Effects of dietary betaine on growth performance, fat deposition and serum lipids in broilers subjected to chronic heat stress. (17th March 2015) - He, Shaojun; Zhao, Shujing; Dai, Sifa; Liu, Deyi; Bokhari, Shehla Gul
Abstract We evaluated the effects of supplementing betaine on growth performance, fat deposition and lipid metabolism status in broilers kept under chronic heat stress. Five hundred and forty chicks were randomly divided into six groups and the two normal temperature groups were held at normal ambient temperature and fed the basal diet (CONT) and basal diet plus 0.1% betaine, respectively. Heat stressed (HS) broilers were held at 32 ± 1°C from days 22 to 42 and fed the basal diet containing variable levels of betaine. Broilers were examined at days 28, 35 and 42 for body weight, feed consumption, fat deposition and serum lipids. The CONT and betaine‐supplemented groups showed higher (P < 0.01 or P < 0.05) feed consumption, body weight gain, and lower feed : gain ratio compared with the HS‐CONT group. Meanwhile, heat stress increased abdominal, intermuscular and subcutaneous fat deposition, whereas the supplemental betaine significantly decreased those compared with the HS‐CONT group. Additionally, betaine supplementation significantly decreased triglyceride, free fatty acids, low‐density lipoprotein cholesterol and high‐density lipoprotein cholesterol compared with HS‐CONT. Chronic HS reduces broiler production performance. However, betaine can reverse these negative effects partially and thus improve carcass composition by changing lipid metabolism.